2015
DOI: 10.18805/ag.v36i4.6668
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties of grape (Vitis vinifera) seed extract and possible extraction techniques - A review

Abstract: Grape (Vitis vinifera) member of family vitaceae, is an excellent source of phenolics, particulary in the skin and seeds. Phenolic compounds have attracted much interest recently, because they are potent antioxidant and exhibit various other physiological activities including anticarcinogenic, antimicrobial, anti-inflammatory and antihypertensive activities associated with reduced risk of chronic diseases like cardiovascular diseases. The method of processing and extraction play a vital role in the quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 60 publications
0
7
0
1
Order By: Relevance
“…Resveratrol (3,4′,5-trihydroxy-stilbene) is a naturally occurring phytoalexin. This compound is found in different pharmaceutical dosage forms, and is recommended as a dietary supplement ( Lekli et al, 2008 ; Bhatt et al, 2012 ; Krithika et al, 2015 ). Previous studies have demonstrated that resveratrol has anti-diabetic properties by the improvement of insulin sensitivity, stimulation of glucose uptake and enhancement of lipolysis and fatty acid β-oxidation ( Breen et al, 2008 ; Vallianou et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol (3,4′,5-trihydroxy-stilbene) is a naturally occurring phytoalexin. This compound is found in different pharmaceutical dosage forms, and is recommended as a dietary supplement ( Lekli et al, 2008 ; Bhatt et al, 2012 ; Krithika et al, 2015 ). Previous studies have demonstrated that resveratrol has anti-diabetic properties by the improvement of insulin sensitivity, stimulation of glucose uptake and enhancement of lipolysis and fatty acid β-oxidation ( Breen et al, 2008 ; Vallianou et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the medicinal plants are being investigated for their antioxidant properties. Phenolic and flavonoid compounds are widespread in plant kingdom where they act as antioxidants and free radical scavengers (Krithika and Naik, 2015). As this is the first report on the antioxidant activity of hydroalcoholic root extract of Diplotaenia turcica.…”
Section: Total Phenolic Content Total Flavonoid Content and Antioxidmentioning
confidence: 92%
“…It is a woody vine plant whose fruits can be eaten raw as a fresh fruit or made into dried fruit, juices and wine; thus, it is of great economic value. Grape cultivation is believed to have originated in Armenia, near the Caspian Sea in Russia, from where it spread westward to Europe and eastward to Iran and Afghanistan [ 9 ]; at present, it is widely grown in tropical, temperate and subtropical regions worldwide. China is home to the most abundant grape genetic resources in the world, where grape cultivation has been conducted for thousands [ 10 ].…”
Section: Introductionmentioning
confidence: 99%